Akademi Memandu Suria Sibu Management System - Ting, Felix Ding Liong; A. Mostafa, Salama (Applied Information Technology And Computer Science, 2022)
Akademi Memandu Suria Sibu is a driving school founded in 2012 and it is located at Jalan Deshon Timur in Sibu. Akademi Memandu Suria Sibu has around 80 people of workers, 20 people are staff workers while 60 people are tutors. Currently, Akademi Memandu Suria Sibu is still using a traditional manual-based system that is paper documentation and logbook to manage their data. This has caused several problems and reduces the effectiveness of their management process. the manual-based management system has a problem of redundancy of data and problem in data retrieval. Besides, the data store in a manual-based system does not have a backup and recovery method. Tutors of the driving school faced difficulty in tracking the learning progress and time schedule of the students. Based on these issues, a responsive web-based driving school management system is developed to solve the problem they faced.